Impact of extroversion and narcissism on in role and extra role performance: Moderating role of impression management motives - Saif Ullah Qureshi; Javeria Ashfaq; Masood Ul Hassan; Muhammad Imdadullah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
The main objective of this research is to highlight the impact of extroversion and narcissism on in-role & extra role performance. In addition, the study also aimed to investigate whether impression management motives would moderate the relationship between personality types (extroversion and narcissist) and performance (in-role & extrarole). For this purpose, this model was developed and empirically tested in the banking industry of Pakistan. The research used self rating and supervisor rating technique to investigate the relationships among study variables. The data was collected through survey from 229 employees of the banking sectors of officer grade-III and above and their ratings from their supervisors. The results multiple regression analysis provided support for all hypotheses. Extroversion was found to be positively related with organizational citizenship behavior-interpersonal (OCB-I), organizational citizenship behavior- organizational (OCB-O) and in-role performance whereas narcissism was found to be negatively associated with OCB-I, OCB-O and in-role performance in the absences of impression management motives. However, the results also suggest that the prediction of OCB-I, OCB-O and in-role performance was positively associated with narcissism when considering the moderating impact of impression management motives. The present study will help managers to understand the behaviors of employees to have positive impact on organizational performance.
Keywords: 330; extroversion; narcissism; impression management; in-role performance; OCB-I; OCB-O